Citrus limon L Burmf peel: Potential anthelmintic agent against Indian Earthworm Eicinia foetida - Upadhyaya, Sristisri (Journal of Drug Delivery and Therapeutics, 2018)
Helminthiasis or worm infection is a common infection in human, affecting a large population of the world. Considering this, anthelmintic activity of citrus limon peel was carried out in this experiment. Citrus limon belongs to family Rutaceae. Ethyl acetate, ethanol and methanol extracts of citrus limonn peel have been evaluated for anthelmintic activity against Indian Earthworm species Eicinia foetida.The results reveal a dose dependent increase in activity of the extracts at 5, 10 and 20 mg/ml concentrations. All the extracts exhibited better activity then standard compound Albendazole. Ethanol extract exhibited highest activity among the extract.Keyword: Anthelmintic activity; Eicinia Foetida, Albendazole.